A qualitative exploration of women's experiences of food insecurity around pregnancy aligned with the socio-ecological model - J. Marshall; L. Davies; Lambeth HDRC; F. Lavelle; N. O'Leary; A.C. Flynn; S. Harding; Z. Bell (Appetite, 2026)

The impacts of alien species on river bioassessment - Maria João Feio; Janine P. da Silva; Robert M. Hughes; Francisca C. Aguiar; Carlos B.M. Alves; Sebastian Birk; Marcos Callisto; Marden S. Linares; Diego R. Macedo; Paulo S. Pompeu; Wayne Robinson; Christian Schürings; et al. (Journal of Environmental Management, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

High-altitude characterization of the Hunga pressure wave with cosmic rays by the HAWC observatory - Ruben Alfaro; César Alvarez; Juan Carlos Arteaga-Velázquez; Arun Babu Kollamparambil Paul; Daniel Avila Rojas; Hugo Alberto Ayala Solares; Rishi Babu; Ernesto Belmont-Moreno; Chad Brisbois; Karen S. Caballero-Mora; Tomás Capistrán; Alberto Carramiñana; et al. (Advances in Space Research, 2024)

LP-18: Challenges and Opportunities in Use of the Minipig for Nonclinical Pharmaceutical Development: Results of the Second IQ DruSafe Minipig Survey - J. Harding; K. Datta; D. Olaharski; D. Clarke; T. Flandre; K. French; M. Leach; S. Mohr; D. Strein; B. Gauthier (Toxicology Letters, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Wind regime changes in the Euro-Atlantic region driven by Late-Holocene Grand Solar Minima - P. Harding; C. Martin-Puertas; J. Sjolte; A. A. Walsh; R. Tjallingii; C. Langdon; S. P. E. Blockley; A. Brauer; P. Langdon; A. M. Milner; R. Muscheler; M. Perez (Climate Dynamics, 2023)

Fish and macroinvertebrate assemblages reveal extensive degradation of the world's rivers - Maria João Feio; Robert M. Hughes; Sónia R. Q. Serra; Susan J. Nichols; Ben J. Kefford; Mark Lintermans; Wayne Robinson; Oghenekaro N. Odume; Marcos Callisto; Diego R. Macedo; Jon S. Harding; Adam G. Yates; et al. (Global Change Biology, 2023)
Rivers suffer from multiple stressors acting simultaneously on their biota, but the consequences are poorly quantified at the global scale. We evaluated the biological condition of rivers globally, including the largest proportion of countries from the Global South published to date. We gathered macroinvertebrate‐ and fish‐based assessments from 72,275 and 37,676 sites, respectively, from 64 study regions across six continents and 45 nations. Because assessments were based on differing methods, different systems were consolidated into a 3‐class system: Good, Impaired, or Severely Impaired, following common guidelines. The proportion of sites in each class by study area was calculated and each region was assigned a Köppen‐Geiger climate type, Human Footprint score (addressing landscape alterations), Human Development Index (HDI) score (addressing social welfare), % rivers with good ambient water quality, % protected freshwater key biodiversity areas; and % of forest area net change rate. We found that 50% of macroinvertebrate sites and 42% of fish sites were in Good condition, whereas 21% and 29% were Severely Impaired, respectively. The poorest biological conditions occurred in Arid and Equatorial climates and the best conditions occurred in Snow climates. Severely Impaired conditions were associated (Pearson correlation coefficient) with higher HDI scores, poorer physico‐chemical water quality, and lower proportions of protected freshwater areas. Good biological conditions were associated with good water quality and increased forested areas. It is essential to implement statutory bioassessment programs in Asian, African, and South American countries, and continue them in Oceania, Europe, and North America. There is a need to invest in assessments based on fish, as there is less information globally and fish were strong indicators of degradation. Our study highlights a need to increase the extent and number of protected river catchments, preserve and restore natural forested areas in the catchments, treat wastewater discharges, and improve river connectivity.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Middle Pleistocene environments, landscapes and tephrostratigraphy of the Armenian Highlands: evidence from Bird Farm 1, Hrazdan Valley - Jenni E. Sherriff; Keith N. Wilkinson; Poppy Harding; Hayley Hawkins; Rhys G. O. Timms; Daniel S. Adler; Emily J. Beverly; Simon P. E. Blockley; Boris Gasparyan; Christina J. Manning; Darren Mark; Samvel Nahapetyan; et al. (Journal of Quaternary Science, 2022)
The significance of the southern Caucasus in understanding Pleistocene hominin expansions is well established. However, the palaeoenvironments in which Palaeolithic occupation of the region took place are presently poorly defined. The Hrazdan river valley, Armenian Highlands, contains a rich Palaeolithic record alongside Middle Pleistocene volcanic, fluvial and lacustrine strata, and thus offer exciting potential for palaeoenvironmental reconstruction. We present the first results of sedimentological, geochemical, tephrostratigraphical and biological (diatoms) study of the sequence of Bird Farm 1, located in the central part of the valley. These data show six phases of landscape development during the interval 440–200 ka. The sequence represents the first quantitative Pleistocene diatom record from the Armenian Highlands and the southern Caucasus, and indicates the persistence of a deep, stratified lacustrine system, with evidence for changing lake productivity that is tentatively linked to climate. Furthermore, major element chemical characterization of visible and crypto‐tephra horizons in the sequence enables the first stages of the development of a regional tephrostratigraphy. Together, the evidence from Bird Farm 1 demonstrates the importance of lacustrine archives in the region for palaeoenvironmental reconstruction and highlights the potential for linkages between archives on both a local and regional scale.

The genetic architecture of target‐site resistance to pyrethroid insecticides in the African malaria vectors Anopheles gambiae and Anopheles coluzzii - Chris S. Clarkson; Alistair Miles; Nicholas J. Harding; Andrias O. O’Reilly; David Weetman; Dominic Kwiatkowski; Martin J. Donnelly (Molecular Ecology, 2021)
Resistance to pyrethroid insecticides is a major concern for malaria vector control. Pyrethroids target the voltage‐gated sodium channel (VGSC), an essential component of the mosquito nervous system. Substitutions in the amino acid sequence can induce a resistance phenotype. We use whole‐genome sequence data from phase 2 of the Anopheles gambiae 1000 Genomes Project (Ag1000G) to provide a comprehensive account of genetic variation in the Vgsc gene across 13 African countries. In addition to known resistance alleles, we describe 20 other non‐synonymous nucleotide substitutions at appreciable population frequency and map these variants onto a protein model to investigate the likelihood of pyrethroid resistance phenotypes. Thirteen of these novel alleles were found to occur almost exclusively on haplotypes carrying the known L995F kdr (knock‐down resistance) allele and may enhance or compensate for the L995F resistance genotype. A novel mutation I1527T, adjacent to a predicted pyrethroid‐binding site, was found in tight linkage with V402L substitutions, similar to allele combinations associated with resistance in other insect species. We also analysed genetic backgrounds carrying resistance alleles, to determine which alleles have experienced recent positive selection, and describe ten distinct haplotype groups carrying known kdr alleles. Five of these groups are observed in more than one country, in one case separated by over 3000 km, providing new information about the potential for the geographical spread of resistance. Our results demonstrate that the molecular basis of target‐site pyrethroid resistance in malaria vectors is more complex than previously appreciated, and provide a foundation for the development of new genetic tools for insecticide resistance management.

ASL expression in ALDH1A1+ neurons in the substantia nigra metabolically contributes to neurodegenerative phenotype - Shaul Lerner; Raya Eilam; Lital Adler; Julien Baruteau; Topaz Kreiser; Michael Tsoory; Alexander Brandis; Tevie Mehlman; Mina Ryten; Juan A. Botia; Sonia Garcia Ruiz; Alejandro Cisterna Garcia; et al. (Human Genetics, 2021)
Argininosuccinate lyase (ASL) is essential for the NO-dependent regulation of tyrosine hydroxylase (TH) and thus for catecholamine production. Using a conditional mouse model with loss of ASL in catecholamine neurons, we demonstrate that ASL is expressed in dopaminergic neurons in the substantia nigra pars compacta, including the ALDH1A1 + subpopulation that is pivotal for the pathogenesis of Parkinson disease (PD). Neuronal loss of ASL results in catecholamine deficiency, in accumulation and formation of tyrosine aggregates, in elevation of α-synuclein, and phenotypically in motor and cognitive deficits. NO supplementation rescues the formation of aggregates as well as the motor deficiencies. Our data point to a potential metabolic link between accumulations of tyrosine and seeding of pathological aggregates in neurons as initiators for the pathological processes involved in neurodegeneration. Hence, interventions in tyrosine metabolism via regulation of NO levels may be therapeutic beneficial for the treatment of catecholamine-related neurodegenerative disorders.

Benthic Invertebrate Indices Show No Response to High Nitrate-Nitrogen in Lowland Agricultural Streams - Thomas P. Moore; Catherine M. Febria; Angus R. McIntosh; Helen J. Warburton; Jon S. Harding (Water, Air, & Soil Pollution, 2021)

Development of a pro-arrhythmic ex vivo intact human and porcine model: cardiac electrophysiological changes associated with cellular uncoupling - Joseph Brook; Min-young Kim; Simos Koutsoftidis; David Pitcher; Danya Agha-Jaffar; Annam Sufi; Catherine Jenkins; Konstantinos Tzortzis; Suofeiya Ma; Richard J. Jabbour; Charles Houston; Balvinder S. Handa; et al. (Pflügers Archiv - European Journal of Physiology, 2020)
We describe a human and large animal Langendorff experimental apparatus for live electrophysiological studies and measure the electrophysiological changes due to gap junction uncoupling in human and porcine hearts. The resultant ex vivo intact human and porcine model can bridge the translational gap between smaller simple laboratory models and clinical research. In particular, electrophysiological models would benefit from the greater myocardial mass of a large heart due to its effects on far-field signal, electrode contact issues and motion artefacts, consequently more closely mimicking the clinical setting. Porcine ( n = 9) and human ( n = 4) donor hearts were perfused on a custom-designed Langendorff apparatus. Epicardial electrograms were collected at 16 sites across the left atrium and left ventricle. A total of 1 mM of carbenoxolone was administered at 5 ml/min to induce cellular uncoupling, and then recordings were repeated at the same sites. Changes in electrogram characteristics were analysed. We demonstrate the viability of a controlled ex vivo model of intact porcine and human hearts for electrophysiology with pharmacological modulation. Carbenoxolone reduces cellular coupling and changes contact electrogram features. The time from stimulus artefact to (-dV/dt) max increased between baseline and carbenoxolone (47.9 ± 4.1–67.2 ± 2.7 ms) indicating conduction slowing. The features with the largest percentage change between baseline and carbenoxolone were fractionation + 185.3%, endpoint amplitude − 106.9%, S-endpoint gradient + 54.9%, S point − 39.4%, RS ratio + 38.6% and (-dV/dt) max − 20.9%. The physiological relevance of this methodological tool is that it provides a model to further investigate pharmacologically induced pro-arrhythmic substrates.

Trialling tools using hand‐weeding, weed mat and artificial shading to control nuisance macrophyte growth at multiple scales in small agricultural waterways - Kathryn E. Collins; Catherine M. Febria; Hayley S. Devlin; Kristy L. Hogsden; Helen J. Warburton; Brandon C. Goeller; Angus R. McIntosh; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2020)
Introduced aquatic macrophytes can dominate small agricultural waterways in summer and autumn becoming a significant management problem. Excessive growth can clog waterways, causing drainage issues and reducing agricultural productivity while in‐stream velocities are reduced and sedimentation increased. Consequently, water managers remove them by mechanical clearance, chemical spray and cutting which can be costly and have negative impacts on in‐stream habitat and ecological health. We trialled three tools to reduce macrophytes: hand‐weeding, weed mat and artificial shading, at a reach‐scale (50 m) and larger‐scale (200–400 m). Hand‐weeding reduced cover in the short‐term, however macrophytes recovered to pre‐treatment levels within one season. Weed mat along the banks was effective at reducing emergent macrophytes, particularly Erythranthe guttata (monkey musk) and Nasturtium microphyllum (watercress). Weed mat lasted for several growing seasons and continued to be effective. Shading over the waterway using polythene markedly reduced submerged macrophytes indicating that heavy shading by riparian plantings could reduce submerged macrophytes in the longer‐term. These results indicate that in the short‐term, weed mat could be used to limit sprawling emergent macrophytes. In the longer‐term, weed mat used in conjunction with riparian planting could provide shading so that macrophyte cover in these small waterways could be reduced and controlled.

Ecological processes mediate the effects of the invasive bloom-forming diatom Didymosphenia geminata on stream algal and invertebrate assemblages - J. P. Bray; C. Kilroy; P. Gerbeaux; F. J. Burdon; J. S. Harding (Hydrobiologia, 2020)

Evaluating practical macrophyte control tools on small agricultural waterways in Canterbury, New Zealand - Kathryn E. Collins; Catherine M. Febria; Helen J. Warburton; Hayley S. Devlin; Kristy L. Hogsden; Brandon C. Goeller; Angus R. McIntosh; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2019)
Excessive macrophytes can cause significant problems in agricultural waterways requiring active management. Conventional control techniques can have a range of adverse effects. We investigated several control tools in two experiments: firstly, we tested eight treatments at a small‐scale (2 m × 2 m). We found intensive hand weeding, weed mat and herbicide spraying to be effective treatments, reducing macrophyte cover to

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Acute toxicity of arsenic to larvae of four New Zealand freshwater insect taxa - Olivier Champeau; Jo Anne E. Cavanagh; Thomas J. Sheehan; Louis A. Tremblay; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2017)
Arsenic, often found in gold deposits, can enter aquatic systems. The toxicity of arsenate (As(V)), the most common valence state of arsenic in freshwater, was assessed on the larvae of four freshwater insect taxa from naturally acidic (pH 5.9) and circumneutral (pH 7.4) New Zealand streams. Insects from the acidic stream were more sensitive to arsenate‐spiked water than those from the circumneutral stream. Early instars ( Deleatidium spp. (Leptophlebiidae) were the most sensitive compared to later instars (3–6 mm) (4‐d LC 50 1.5 and 3.5 mg/L, respectively) or to the stonefly Zelandobius spp. (Gripopterygidae) (4‐d LC 50 2.5 mg/L). The cased caddisflies Pycnocentria spp. (Conoesucidae) and Helicopsyche spp. (Helicopsychidae) from circumneutral stream were the most tolerant (4‐d LC 50 45.4 and 113 mg/L, respectively). The 14‐day arsenic LC 10 and LC 50 for Deleatidium spp. late instars exposed to mining‐impacted water were 0.12 and 0.36 mg/L, respectively.

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Long-Term Trends of Nutrients and Phytoplankton in Chesapeake Bay - L. W. Harding; C. L. Gallegos; E. S. Perry; W. D. Miller; J. E. Adolf; M. E. Mallonee; H. W. Paerl (Estuaries and Coasts, 2016)

Initial evaluations of a Gulf of Mexico/Caribbean ocean forecast system in the context of the Deepwater Horizon disaster - Edward D. Zaron; Patrick J. Fitzpatrick; Scott L. Cross; John M. Harding; Frank L. Bub; Jerry D. Wiggert; Dong S. Ko; Yee Lau; Katharine Woodard; Christopher N. K. Mooers (Frontiers of Earth Science, 2015)

“Agro-meteorological indices and climate model uncertainty over the UK” - A. E. Harding; M. Rivington; M. J. Mineter; S. F. B. Tett (Climatic Change, 2015)

Variable survival across low pH gradients in freshwater fish species - P. G. Jellyman; J. S. Harding (Journal of Fish Biology, 2014)
A series of 14 day experiments was conducted on five common New Zealand fish species (redfin bully Gobiomorphus huttoni , inanga Galaxias maculatus , brown trout Salmo trutta , longfin eel Anguilla dieffenbachii and koaro Galaxias brevipinnis ) to assess the effect of pH on survival and changes in body mass. No species survived in water of pH pH 4·5, G. maculatus larvae were also tested and had high mortality at this pH . Results suggest that adults are tolerant of low‐ pH waters; however, successful remediation of anthropogenically acidified streams will require an understanding of the susceptibility to low pH on different life cycle stages.

Trade-off in ecosystem services of the Somerset Levels and Moors wetlands - M. C. Acreman; R. J. Harding; C. Lloyd; N. P. McNamara; J. O. Mountford; D. J. Mould; B. V. Purse; M. S. Heard; C. J. Stratford; S. J. Dury (Hydrological Sciences Journal, 2011)

Adverse foraging conditions may impact body mass and survival of a high Arctic seabird - Ann M. A. Harding; Jorg Welcker; Harald Steen; Keith C. Hamer; Alexander S. Kitaysky; Jérôme Fort; Sandra L. Talbot; Leslie A. Cornick; Nina J. Karnovsky; Geir W. Gabrielsen; David Grémillet (Oecologia, 2011)

Carbon Cycling in Floodplain Ecosystems: Out-Gassing and Photosynthesis Transmit Soil δ13C Gradient Through Stream Food Webs - Duncan P. Gray; Jon S. Harding; Bo Elberling; Travis Horton; Tim J. Clough; Mike J. Winterbourn (Ecosystems, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

Multi-scale calculation and global-fit analysis of hydrodynamic properties of biological macromolecules: determination of the overall conformation of antibody IgG molecules - D. Amorós; A. Ortega; S. E. Harding; J. García de la Torre (European Biophysics Journal, 2010)

Structure and heterogeneity of gliadin: a hydrodynamic evaluation - Shirley Ang; Jana Kogulanathan; Gordon A. Morris; M. Samil Kök; Peter R. Shewry; Arthur S. Tatham; Gary G. Adams; Arthur J. Rowe; Stephen E. Harding (European Biophysics Journal, 2010)

Infectious exposure in the first year of life and risk of central nervous system tumors in children: analysis of day care, social contact, and overcrowding - N. J. Harding; J. M. Birch; S. J. Hepworth; P. A. McKinney (Cancer Causes & Control, 2009)

Design and application of two novel degenerate primer pairs for the detection and complete genomic characterization of potyviruses - C. Ha; S. Coombs; P. A. Revill; R. M. Harding; M. Vu; J. L. Dale (Archives of Virology, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Evaluation of potato production best management practices - Bryan G. Hopkins; Donald A. Horneck; Mark J. Pavek; Brad D. Geary; Nora L. Olsen; Jason W. Ellsworth; George D. Newberry; Jeff S. Miller; Robert E. Thornton; Gale W. Harding (American Journal of Potato Research, 2007)

Longitudinal patterns in benthic communities in an urban stream under restoration - Tanya J. Blakely; Jon S. Harding (New Zealand Journal of Marine and Freshwater Research, 2005)
Okeover Stream, on the University of Canterbury campus in Christchurch, New Zealand, has been the subject of restoration efforts since 1998. Our study focused on quantifying the response of this urban stream to current restoration efforts. Initially, physico‐chemical conditions and biological communities at three sites along the Okeover Stream were compared with three physically similar sites on each of nearby Waimairi Stream and Avon River. General physical and chemical parameters were similar in all streams with circum‐neutral pH, specific conductivity ranging from 167 to 173 μS/cm, dissolved oxygen ranging from 9.0 to 9.2 mg/litre, low turbidity, and similar hydrological conditions. However, analysis of heavy metals in the sediment showed mean lead (Pb) concentrations in Okeover and Waimairi Streams exceeded ANZECC ISQG‐low trigger values (86.9 and 83.7 mg/kg, respectively), whereas Avon River sediment Pb levels (27.3 mg/ kg) were below trigger values. Benthic taxonomic richness did not differ significantly among the three streams. However, Okeover Stream community was dominated by the amphipod Paracalliopefluviatilis, whereas in Waimairi Stream and Avon River the gastropod snails Potamopyrgus antipodarum and Physella acuta were the dominant benthic fauna. A further assessment made at six sites along 1200 m of Okeover Stream showed no distinct longitudinal patterns in physical or chemical conditions, but there was a strong pattern in benthic macroinvertebrate communities. Taxonomic richness and caddisfly diversity increased downstream, with twice as many taxa at the most downstream site than the uppermost sampling site. In upper reaches, copper (Cu), Pb, and zinc (Zn) concentrations in sediments all exceeded ANZECC ISQG‐low trigger values. Despite ongoing restoration efforts in Okeover Stream, sedimentation, the presence of high heavy metal concentrations, intermittent flows in headwaters, and possible barriers to adult recolonisation seem to be having a continuing negative impact on benthic communities, especially in the headwaters.

Larval lobster ( Homarus americanus ) distribution and drift in the vicinity of the Gulf of Maine offshore banks and their probable origins - G. C. HARDING; K. F. DRINKWATER; C. G. HANNAH; J. D. PRINGLE; J. PRENA; J. W. LODER; S. PEARRE; W. P. VASS (Fisheries Oceanography, 2005)
Surveys for lobster larvae in offshore waters of the north‐eastern Gulf of Maine in 1983, 1987 and 1989 confirm that local hatching occurs mainly at depths

Sugarcane bacilliform virus encapsidates genome concatamers and does not appear to integrate into the Saccharum officinarum genome - R. J. Geijskes; K. S. Braithwaite; G. R. Smith; J. L. Dale; R. M. Harding (Archives of Virology, 2004)

Sequence analysis of an Australian isolate of sugarcane bacilliform badnavirus - R. J. Geijskes; K. S. Braithwaite; J. L. Dale; R. M. Harding; G. R. Smith (Archives of Virology, 2002)

Lidar remote sensing of above‐ground biomass in three biomes - Michael A. Lefsky; Warren B. Cohen; David J. Harding; Geoffrey G. Parker; Steven A. Acker; S. Thomas Gower (Global Ecology and Biogeography, 2002)
Estimation of the amount of carbon stored in forests is a key challenge for understanding the global carbon cycle, one which remote sensing is expected to help address. However, estimation of carbon storage in moderate to high biomass forests is difficult for conventional optical and radar sensors. Lidar ( li ght d etection and r anging) instruments measure the vertical structure of forests and thus hold great promise for remotely sensing the quantity and spatial organization of forest biomass. In this study, we compare the relationships between lidar‐measured canopy structure and coincident field measurements of above‐ground biomass at sites in the temperate deciduous, temperate coniferous, and boreal coniferous biomes. A single regression for all three sites is compared with equations derived for each site individually. The single equation explains 84% of variance in above‐ground biomass ( P

Promoters derived from banana bunchy top virus-associated components S1 and S2 drive transgene expression in both tobacco and banana - S. Hermann; D. Becker; R. Harding; J. Dale (Plant Cell Reports, 2001)

Progress in understanding of land surface/atmosphere exchanges at high latitudes - R. J. Harding; S.-E. Gryning; S. Halldin; C. R. Lloyd (Theoretical and Applied Climatology, 2001)

The role of corticotrophin-releasing factor in stress-induced relapse to alcohol-seeking behavior in rats - A. D. Lê; S. Harding; W. Juzytsch; J. Watchus; U. Shalev; Y. Shaham (Psychopharmacology, 2000)

5′-Anchored simple-sequence repeat primers are useful for analysing potato somatic hybrids - D. Matthews; J. McNicoll; K. Harding; S. Millam (Plant Cell Reports, 1999)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Mapping of the gene encoding the B56β subunit of protein phosphatase 2A (PPP2R5B) to a 0.5-Mb region of chromosome 11q13 and its exclusion as a candidate gene for multiple endocrine neoplasia type 1 (MEN1) - S. A. Forbes; A. A. J. Pannett; J. H. D. Bassett; B. Harding; C. Wooding; R. V. Thakker; R. Butler; D. Ogilvie; R. Anand; P. Gaudray; G. Weber; C. Larsson; et al. (Human Genetics, 1997)

A polydisperse linear random coil model for the quaternary structure of pig colonic mucin - Kornelia Jumel; Fiona J. J. Fogg; David A. Hutton; J. P. Pearson; Adrian Allen; S. E. Harding (European Biophysics Journal, 1997)

Characterisation of the low affinity interaction between rat cell adhesion molecules CD2 and CD48 by analytical ultracentrifugation - H. Silkowski; S. J. Davis; A. Neil Barclay; Arthur J. Rowe; Stephen E. Harding; Olwyn Byron (European Biophysics Journal, 1997)

Low temperature solution behaviour of Methylophilus methylotrophus electron transferring flavoprotein: a study by analytical ultracentrifugation - H. Cölfen; S. E. Harding; Emma K. Wilson; Nigel S. Scrutton; Donald J. Winzor (European Biophysics Journal, 1997)

A slot-blot hybridisation method for screening somatic hybrids - D. Matthews; K. Harding; M. J. Wilkinson; S. Millam (Plant Molecular Biology Reporter, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

A gene tree for β-globin sequences from melanesia - R. M. Harding; S. M. Fullerton; R. C. Griffiths; J. B. Clegg (Journal of Molecular Evolution, 1997)

Detection and characterization of pangola stunt Fijivirus from Australia using cloned cDNA probes - M. Karan; J. L. Dale; M. F. Bateson; R. M. Harding; D. S. Teakle (Archives of Virology, 1994)